Pharmacokinetics and Optimal Dose Selection of Cefazolin for Surgical Prophylaxis of Pediatric Patients. (9th December 2020) - Schmitz, Michael L.; Rubino, Christopher M.; Onufrak, Nikolas J.; Martinez, Diana Valencia; Licursi, Diane; Karpf, Angela; Cetnarowski, Wes
Abstract: Cefazolin is an antibiotic frequently used for perioperative prophylaxis. Data from healthy adults and pediatric surgery patients were pooled to refine a previously developed population pharmacokinetic (PK) model and to determine the optimal body weight cutoff for selecting fixed doses of either 1 or 2 g cefazolin to produce exposures in pediatric surgery patients similar to a single 2‐g dose in adults. Regardless of dose used, cefazolin was well tolerated in pediatric patients. A total of 1102 plasma samples from 62 patients from 3 studies were available to assess the previous model. The pooled data set allowed for simplification of the model such that allometrically scaled clearance and volume parameters were found to provide a robust fit while removing unnecessary covariate relationships. Monte Carlo simulations using the final cefazolin population PK model suggested an optimal weight cutoff of 50 kg, in contrast to the previously suggested 60 kg for a single 2‐g dose. Patients at or above this 50‐kg cutoff would receive a 2‐g dose of cefazolin, and those below 50 kg but ≥25 kg would receive a 1‐g dose of cefazolin.